Perceptual versus conceptual interference and pattern separation of verbal stimuli in young and older adults. Issue 6 (18th March 2013) - Ly, Maria; Murray, Elizabeth; Yassa, Michael A.
Abstract Recently, several studies have strongly suggested that age‐related decline in episodic memory is associated with deficits in hippocampal pattern separation (orthogonalizing overlapping experiences using distinct neural codes). The same studies also link these deficits to neurobiological features such as dentate/CA3 representational rigidity and perforant path loss. This decline in pattern separation is thought to underlie behavioral deficits in discriminating similar stimuli on pictorial tasks. Similar pictorial stimuli invoke interference both in the perceptual and conceptual domains, and do not allow one to be disentangled from another. For example, it is very difficult to design a set of pictorial stimuli that are perceptually similar yet conceptually unrelated. Verbal stimuli, on the other hand, allow experimenters to independently manipulate conceptual and perceptual interference. We tested discrimination on conceptually similar (semantically related) and perceptually similar (phonologically related) verbal stimuli in young (mean age 20) and older adults (mean age 69), and find that older adults are selectively impaired in perceptual pattern separation. This deficit was not secondary to failure in working memory, attention, or visual processing. Based on past studies, we suggest that perceptual discrimination relies on recollection while conceptual discrimination relies more on gist. Our results fit well within the notion that recollection but not familiarity (i.e. gist) is impaired in older adults, and suggests that the impairment observed in pictorial tasks may be driven mostly by failure in perceptual and not conceptual pattern separation. © 2013 Wiley Periodicals, Inc.